The journalist's toolbox : a guide to digital reporting and AI - Reilley, Mike, 1965- (Routledge Taylor & Francis Group, 2024)
"Focusing on the 'how' and 'why' of digital reporting, this interactive textbook equips readers with all the skills they need to succeed in today's multimedia reporting landscape. The Journalist's Toolbox is an extension of the JournalistsToolbox.ai website which provides links to tools, organized by beats and topics, as well as social channels, a newsletter, and more than 75 training videos relevant to journalists. This handbook offers a deep dive into these digital resources, explaining how they can be manipulated to build multimedia stories online and in broadcast. It covers all the basics of data journalism, fact-checking, using social media, editing and ethics, as well as video, photo, and audio production and storytelling. The book considers digital journalism from a global perspective, including examples and interviews with journalists from around the world. Packed full of hands-on exercises and insider tips, The Journalist's Toolbox is an essential companion for students of Online/Digital Journalism, Multimedia Storytelling and Advanced Reporting. This book will also make an ideal reference for practicing journalists looking to hone their craft. This book is supported by training videos, interactive charts and a pop-up glossary of key terms which are available as part of an interactive e-book+ or online for those using the print book"--